Educational management strategies for strengthening teacher ethics - Ramón-Cabrera, Fani (2022)
This research responds to the need to improve ethical behavior, interpersonal relationships and the practice of values ​​in private Franciscan educational institutions. In order for this difficulty to be understood and incorporated as practice in the classroom, the application of a program of educational management strategies was proposed to strengthen teaching ethics oriented towards compliance with institutional norms, collaborative work and practice of managerial skills within the framework of the principle’s teacher ethics. The methodology is of a quasi-experimental type with two groups: experimental and control selected through a non-probabilistic sampling of 35 teachers in each group. A pre-test and post-test were used with a questionnaire validated through expert judgment, Cronbach's Alpha was 0.959, which verifies the reliability of the questionnaire. The program was developed in 15 sessions. The data was processed using descriptive and inferential statistics with the non-parametric Mann Whitney SPSS U test. The results verified changes in the ethical behavior and ways of acting of the teachers, significant differences were found; in the experimental group the fair and good levels decreased; increased the very good level by 91.40%. It was concluded that the application of the program improved the pedagogical practices of teachers with thoughts and feelings of Franciscan philosophy to have a behavior based on justice, peace and ecology. Ideas that are reflected in reality and in decision-making oriented towards the well-being of others and oneself.